Rare giant epithelioid inflammatory myofibroblastic sarcoma of the abdominal cavity in a child: a case report and review of the literature - Li, Jinzhou; Su, Haixing; Zhang, Sheng; Chen, Xianyun; Hou, Chongzhi; Cheng, Tao (Frontiers in Oncology, 2024)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is a distinct subtype of inflammatory myofibroblastoma tumor (IMT) that is recognized as a rare malignant tumor characterized by anaplastic lymphoma kinase (ALK) positivity, significant aggressiveness, treatment challenges, and a poor prognosis. We report on the case of an 8-year-old boy presenting with abdominal pain and vomiting. Computed tomography (CT) of the abdomen revealed a large tumor, and the pathology results following a biopsy confirmed the diagnosis of EIMS. The patient underwent radical tumor resection, and genetic testing identified the presence of the RANBP2–ALK fusion. To our knowledge, this represents the largest pediatric case of abdominal EIMS documented in the literature. Currently, there is no standard therapy for EIMS; however, existing studies advocate for the use of ALK tyrosine kinase inhibitors (TKIs) in its treatment. This case was reported to be in remission following treatment with crizotinib, thereby contributing to the understanding of the specific pathology of EIMS and facilitating accurate diagnosis and targeted therapy.